Complications in Implementing the European Order for Payment and the European Account Preservation Order - Glushkova, Мaria (Law Journal of New Bulgarian University, 2023)
The article attempts to present the complications that arise in our country with the scopeand implementation of European orders for payment – Regulation 1896/2006, issued in another member state of the European Union and European bank account preservation orders – Regulation 655/2014. The above two acts are examined in their entirety and totality, some of the controversial points in relation to their application and enforcement in our country are discussed (problems related to the regularity of their service; the revaluation of the amounts due; the excess security and disproportionality; the amount of court fees and costs, including those incurred in the enforcement phase; the occurrence of prescription or peremption, etc.). The collision between the European legal norms and those of the national legislation is highlighted, the shortcomings and gaps are pointed out, as well as the complications that arise and hinder the application of the regulations. Proposals de lege ferenda have been made.